(4Z, 15Z)‐Octadecadienoic Acid Inhibits Glycogen Synthase Kinase‐3β and Glucose Production in H4IIE Cells. Issue 3 (13th February 2017) - Yoshida, Jun; Uesugi, Shota; Kawamura, Tetsuaki; Kimura, Ken‐ichi; Hu, Dawei; Xia, Shuang; Toyooka, Naoki; Ohnishi, Masao; Kawashima, Hideki
Abstract: Many uncommon non‐methylene‐interrupted fatty acids (NMI FA) are present in limpet gonads, but their biological properties remain unknown. To investigate new biological effects of naturally occurring NMI FA in eukaryotic cells, the biological activities of structurally analogous (4 Z, 15 Z )‐octadecadienoic acid (1 ), (9 Z, 20 Z )‐tricosadienoic acid (2 ), and (12 Z, 23 Z )‐hexacosadienoic acid (3 ) were examined by using a yeast‐based drug‐screening system using the Ca 2+ ‐sensitive mutant strain, Saccharomyces cerevisiae ( zds 1Δ erg 3Δ pdr 1Δ pdr 3Δ). Among1 –3, 1 showed restored growth activity at a dose of 80 µg/disc in the mutant yeast strain. This phenotype suggests that1 suppresses Ca 2+ ‐signaling of the mutant yeast through inhibition of glycogen synthase kinase‐3β (GSK‐3β) or calcineurin pathways or both. From this result, the inhibitory activity of1 –3 against GSK‐3β was further determined.1 –3 showed potent inhibitory activity against GSK‐3β with IC50 values ranging from 8.7 to 21.9 µM. Inhibition of GSK‐3β reduces gene expression of the gluconeogenic key enzymes in liver, so we analyzed glucose production in rat hepatoma H4IIE cells to assess GSK‐3β inhibitory activity of1 –3 . Acid1 inhibited glucose production at 25 µM in H4IIE cells. Our results would open up new possibilities for an anti‐diabetic effect of1 and might provide important insights into understanding the biological properties of naturally occurring NMI FA.